Dying Light: War and Trade of the Separatist-Controlled Areas of Ukraine - Artem Kochnev (The Vienna Institute for International Economic Studies (wiiw), 2019)
The paper investigates how war and the war-related government policies affected economic activity of the separatist-controlled areas of Ukraine. The paper applies a quasi-experimental study design to estimate the impact of two events on the separatist-controlled areas the introduction of the separatist control and the introduction of the second round of the trade ban, which was imposed by the government of Ukraine on the separatist-controlled territories in 2017. Using a difference-in-difference estimation procedure that controls for the yearly and monthly effects, individual fixed effects, and the region-specific time shocks, the study finds that the separatist rule decreased the economic activity by 38% in the Donetsk region and 51% in the Luhansk region according to the preferred specifications. At the same time, the trade ban of the year 2017 against the major industrial enterprises of the separatist-controlled areas decreased luminosity by 20%. The paper argues that the trade disruptions due to the war actions were nested within the negative effect of the separatist rule and accounted for half of it.
Keywords: D74; E01; E20; F51; 330; costs of war; satellite data; trade; Ukraine crisis; political economy